1986
DOI: 10.1002/ajh.2830210211
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary antithrombin III deficiency: Case report and review of recent therapeutic advances

Abstract: We report on a newly diagnosed family with hereditary antithrombin III deficiency, with thromboembolic complications in the propositus. Both the propositus and his asymptomatic sister had decreased plasma levels of antithrombin III antigen and activity (28-52% of normal with good agreement between functional and immunologic assays). The propositus developed deep venous thrombosis, followed by massive pulmonary emboli despite heparin therapy and was treated with streptokinase and heparin with excellent results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In one of our cases it was noted in the chart that it took 5 days until APTT increased above 50 s, but the daily dose of heparin was never higher than 40,000 iu. The doses have not been very high in several of the cases of "heparin resistance" previously reported: 30,000 iu (1), 36,000 iu (4), 30-40,000 iu (14), 35,000 iu (15), 33,600 iu (16), 645 iu/kg (17), the exception being 70,000 iu (3). The latter case had a low AT III activity, less than 30%.…”
Section: Discussionmentioning
confidence: 94%
“…In one of our cases it was noted in the chart that it took 5 days until APTT increased above 50 s, but the daily dose of heparin was never higher than 40,000 iu. The doses have not been very high in several of the cases of "heparin resistance" previously reported: 30,000 iu (1), 36,000 iu (4), 30-40,000 iu (14), 35,000 iu (15), 33,600 iu (16), 645 iu/kg (17), the exception being 70,000 iu (3). The latter case had a low AT III activity, less than 30%.…”
Section: Discussionmentioning
confidence: 94%
“…Six of the seven patients now reported in the literature (Fairfax & Ibbotson, 1985;Eyster & Parker, 1985;Miller et al 1986; this report) have shown increments of ATIII activity, in the chromogenic assay and/or antigenic assay, while receiving danazol and warfarin therapy. This is the first report including trial with danazol alone, documenting discordant results from the two assay systems: ATIII activity remaining almost unchanged by the chromogenic assay when warfarin was ceased, but a 42% decrease in activity was recorded by the antigenic assay; the significance of this observation is not known, but it is because of this observation that the danazol therapy was ceased.…”
mentioning
confidence: 78%
“…The afflicted family members with a history of thromboembolism are generally advised life-long oral anticoagulant therapy (Cosgriff et al 1983), but because of the potential bleeding problems with this form of therapy, there is a need for an alternative long-term, treatment. Danazol, an attenuated androgen, has been shown to increase plasma concentrations of ATIII in women with endometriosis (Laurel1 & Rannevik 1979) and some recent reports (Fairfax & Ibbotson 1985;Eyster & Parker 1985;Miller et al 1986) have documented sustained rise in ATIII levels in patients with familial ATIII deficiency when danazol was added to the warfarin therapy. In this report we describe our experience in a man with familial ATIII deficiency treated with danazol, with and without warfarin.…”
mentioning
confidence: 99%
“…The antithrombin III level increased from 35 to 56% and no thromboses occurred. Treatment of at least 10 other patients with inherited antithrombin III deficiency with either stano zolol or danazol have been reported [10,11,[20][21][22], In 9 out of 10 a significant increase in the antithrombin III level was observed; how ever, in 2 patients deep venous thrombosis occurred while on therapy despite the in crease in antithrombin III level [20]. Treat ment with oxymethalone, another anabolic steroid, has also been reported to increase antithrombin III levels in patients with inher ited antithrombin III deficiency [23], Gonzalez et al [9] were the first to report the administration of a synthetic androgen to a patient with protein C deficiency.…”
Section: Discussionmentioning
confidence: 99%